Genome-wide copy number variations in Bhutia equine breed using SNP genotyping data - SHARMA, NITESH KUMAR; SINGH, PRASHANT; SAHA, BIBEK; BHARDWAJ, ANURADHA; IQUEBAL, MIR ASIF; PAL, YASH; NAYAN, VARIJ; JAISWAL, SARIKA; GIRI, SHIV KUMAR; LEGHA, RAM AVATAR; BHATTACHARYA, T K; KUMAR, DINESH; et al. (The Indian Journal of Animal Sciences, 2023)
Copy number variants (CNVs) have dynamic potential and evolutionary significance like other genetic variants, namely, single nucleotide polymorphisms, InDels, short tandem repeat polymorphisms, inversion variants, etc. Discovering CNVs leads to further speculation that the genomic DNA contains more changes than previously thought and contributes to the phenotypic variation. CNVs are big DNA fragments (> 1 kb) being duplicated or deleted. A bridge between CNVs and phenotypic variations supports CNVs to be utilized in GWAS, which are currently mostly based on SNPs. CNV, which refers to the structural differences, influence gene expression and can be an indicator of numerous traits for improvement. There is a severe dearth of research on CNVs in animals, especially equine. The present study investigates the genomes of the Bhutia Equine breed for genome-wide discovery of CNVs using theAxiom™ Equine Genotyping Array chip for a better understanding of its traits which had been unexplored till date. A total of 619 CNVs from 20 Bhutia equines were identified with the median and average size as 49.394 kb and 114.955 kb, respectively. Total 225 frequent CNVRs with > 1% CNV frequency were identified among them along with singleton type. These CNVRs contained 361 genes in all. The information obtained on genomic variation could be utilized to identify economically advantageous genetic features in Bhutia equine breed.